Synthesis of Chiral Triazole-Based Halogen Bond Donors - Kaasik, Mikk; Kaabel, Sandra; Kriis, Kadri; Järving, Ivar; Kanger, Tõnis (Synthesis, 2019)
The number of applications that use halogen bonding in the fields of self-assembly, supramolecular aggregation, and catalysis is growing. However, the accessibility of chiral halotriazoles shows that there is still a lot more to explore. The simple click-chemistry is applied for the straightforward synthesis of enantiomerically pure mono- and bidentate as well as multifunctional iodotriazole-based XB donors. The methodology is characterized by a wide variability due to easy access of chiral azides.
Keywords: click chemistry; nitrogen heterocycles; halogen bonds; hydrogen bonds; chiral compounds